Peran ASEAN dalam Mempengaruhi Indonesia untuk Meratifikasi Asean Agreement on Transboundary Haze Pollution (AATHP) - Suartini, Ni Putu Gita; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT Since the haze crisis becomes a transnational issue in the Southeast Asia region, ASEAN has formulated an initiative by creating a partnership within a framework of the ASEAN Agreement on Transboundary Haze Pollution (AATHP) in 2002 as a form to overcome the haze issue. However, Indonesia as one of the country which is causing the haze issue has become the last country to ratify this agreement. As the research question is how ASEAN does encourage Indonesia to ratify AATHP, this research aims to analyze the dynamic of the role performed by ASEAN using the concept of the role and function of international organizations. This concept is able to analyze the role of ASEAN as an independent actor and the efforts by ASEAN as an arena that also explains the function of ASEAN for its role. The role of ASEAN is then able to influence Indonesia to ratify AATHP. The success of the ratification carried out by Indonesia is inseparable from the power by ASEAN which then gives the ability to shame to Indonesia as the last country to ratify AATHP. This research uses descriptive qualitative method using official documents issued by ASEAN and related journals as data sources. Keywords: Indonesia, ASEAN, Role and Function, Asean Agreement on Transboundary Haze Pollution (AATHP)